Antimicrobial activities of spirooxindolopyrrolidine tethered dicarbonitrile heterocycles against multidrug resistant nosocomial pathogens - Natarajan Arumugam; Abdulrahman I. Almansour; Raju Suresh Kumar (Elsevier, 2021)
Background: Microbial infections together with rising drug resistance pose a threat to immunocompromised individual. In this perspective, compounds with spirooxindolopyrrolidine play a significant role in research on antimicrobial drug delivery research owing to their various pharmaceutical activities. Spiroheterocyclic compounds are present in number of medications as active motif due to their exceptional structural properties which enable for easy interaction with the protein of the biological target. Inspired by this biological precedent encouraged to synthesize a new class of dispirooxindole fused pyrrolidine heterocycles via a three-component cycloaddition strategy. Materials and Methods: The new class of structurally intriguing spirooxindolopyrrolidines were synthesized through three component cycloaddition process and the structure of products were assigned through spectroscopic analysis. The newly synthesized compounds were assessed for their antimicrobial sensitivity test with standard Kirby Bauer method with common drugs. Results: The structurally unexplored hybrid heterocycles fused spirooxindolopyrrolidine exhibited excellent antimicrobial activity against the common nosocomial microbial pathogens. Of four compounds, the compound bearing a chlorine atom on the aryl ring (4a) exhibited significant antimicrobial activity (zone of inhibition: 9.00 ± 1.00-17.00 ± 0.35 mm and MIC: 16.00-256.00 μg/mL) against selected nosocomial infection causing microbial pathogens. Hence, the compound 4a has been considered as an effective drug of interest in therapeutic field for compacting infectious diseases causing pathogens. Conclusion: With an aim of developing more effective and economically more affordable antimicrobial leads with a unique mechanism of action, we have designed and synthesized structurally diverse spirooxindolopyrrolidine tethered hybrids that has been assayed against multidrug resistant nosocomial pathogens. The regioisomer having chloro substituted on the phenyl ring showed potent activity when compared to standard drug. Future studies are required to explicate the pharmacological properties of new hybrid heterocycles that have been synthesized in our laboratory for the novel therapeutic development.